Source-to-sink magnetic properties of NE Saharan dust in Eastern Mediterranean marine sediments: review and paleoenvironmental implications - Larrasoaña, Juan C.; Roberts, Andrew P.; Liu, Qingsong; Lyons, Richard; Oldfield, Frank; Rohling, Eelco J.; Heslop, David (Frontiers in Earth Science, 2015)
We present a review of the magnetic properties of NE Saharan dust that was conducted, following a source-to-sink approach, to unravel the paleoclimatic significance of environmental magnetic records from Eastern Mediterranean marine sediments. Our synthesis indicates that pedogenic hematite, which formed during past wetter Green Sahara periods (GSPs), is the most common magnetic mineral in Eastern Mediterranean marine sediments as a result of its eolian transportation, along with smaller amounts of lithogenic hematite, from the NE Sahara. Coupled with the limited impact of reductive sedimentary diagenesis on hematite abundances in Eastern Mediterranean Sea sediments, this indicates that hematite concentrations provide reliable quantitative estimates of NE Saharan dust supply. Our results indicate that variations in NE Saharan dust supply record an on-off mechanism in which a key control on eolian input is provided by the monsoon-driven spread and retreat of savannah vegetation through the Sahara. Magnetite/maghemite is also a common magnetic mineral in NE Saharan dust, and also formed mainly pedogenically during GSPs but in much smaller amounts compared to hematite. Limited production of magnetite/maghemite in the source area during GSPs, along with the later imprint of diagenetic processes, indicates that magnetite/maghemite abundances cannot be used to estimate dust inputs from the NE Sahara. Goethite cannot be used either to estimate variations in NE Saharan dust supply, because its occurrence in Eastern Mediterranean marine sediments also appears to be linked to fluvial inputs. Our results reinforce the view that a source-to-sink approach should be routinely conducted in environmental magnetic studies to understand the complex combination of processes involved in the production, transportation, sedimentation and diagenetic evolution of magnetic minerals in sedimentary environments.